Kriemhilds Rache - Fährmann, Willi,Blaebst, Werner (Thienemann, 1988)
In this retelling of a story from the Nibelungenlied, Kriemhild, the wife of Siegfried, takes revenge for his murder.
Keywords: Kinderbuch; Kriemhild; Folklore; German language materials; Nibelungen; Revenge; Siegfried (Legendary character)